Reflection of P-wave and SV-wave in a generalized two temperature thermoelastic half-space - Santra, Sutapa; Lahiri, Abhijit; Das, Nayon Chandra (Zielona Góra: Uniwersytet Zielonogórski)
In this work the theory of two temperature generalized thermoelasticity has been used to investigate the problem of reflection of P-wave and SV-wave in a half space when the surface is i) thermally insulated or ii) isothermal. The ratios of the reflection coefficient to that of the incident coefficient for different cases are obtained for P-wave and SV-waves. The results for various cases for the conductive and dynamical temperature have been compared. The results arrived at in the absence of the thermal field (elastic case) have also been compared with those in the existing literature. Finally, the results for various cases have been analyzed and depicted in graphs.
Keywords: P-wave; SV-wave; conductive temperature; dynamical temperature; second sound